Optimalisasi Kewirausahaan Bersama Berbasis Ramah Lingkungan Pada Kader PKK di Desa Trasan Kabupaten Magelang - Fawwaz Jaerawibawa; Rizka Zulfa Amalia; Izralia Gholiyah; Triastuti Sulistyaningsih; Bagawat Gita (Jurnal Bina Desa, 2025)
Trasan Village in Magelang Regency is the leading village in Bandongan District in terms of opening up opportunities for the birth of Micro, Small and Medium Enterprises (MSMEs). However, MSME actors in the village are still dominated by men so that the role of women in the village community economy is still not optimal and there is the problem of MSME waste which has not been managed properly. The UNNES service team helped overcome this problem by creating an environmentally friendly entrepreneurship development program involving village PKK cadres to create an inclusive and environmentally responsible business climate. The service method used is training for a program for utilizing MSME waste oil into aromatherapy candle products and assistance for planning and business marketing programs for these aromatherapy candle products. The results of this program have increased the understanding of Trasan Village PKK cadres regarding the use of waste into products of economic value by 78% and understanding regarding business planning and marketing by 86%. PKK cadres have also been assisted with business consultations, creating business legality and marketing strategies by Village MSME facilitators.